(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
يهدف البحث إلى دراسة تأثير المقاومة التسلسلية والتفرعية على أداء الخلايا الشمسية بدلالة درجات حرارة مختلفة تحت تأثير الضوء وفي الظلام، وذلك من خلال دراسة المميز تيار- جهد للخلية الشمسية في مجال حراري واسع (233K-373K)، ومن ثم محاكاة هذه المميزات لإيجاد قيم المقاومة التسلسلية والتفرعية. جرى في هذا البحث دراسة عينة على شكل خلية شمسية (وصلة من النوع p-i-n) مكونة من طبقة من السيليسيوم النقي متوضعة بين بنية السيليسيوم الميكروبلوري والسيليسيوم اللابلوري المهدرج والمشار إليها اختصاراً بالرمز c(a)-Si:Hµ، سعياً لتعزيز أداء خلايا السيليسيوم اللابلورية المهدرجة. بينت النتائج أن تأثير المقاومة التسلسلية على أداء الخلية ضعيف، بينما تلعب المقاومة التفرعية دوراً سلبياً في أداء الخلية مع ازدياد درجة الحرارة حيث تؤدي إلى تراجع قيمة معامل الملء وبالتالي إلى تراجع في الاستطاعة المأخوذة من الخلية. أي إنه في درجات الحرارة العالية يجب تحسين قيمة هذه المقاومة لكي يتحسن أداء الخلية. The goal of this research is to study the effect of serial and parallel resistance on the performance of solar cells in terms of different temperatures under the influence of light and in darkness. This has been done by studying the current - voltage characteristics of a solar cell at the temperature range between 233 K and 373 K. These characteristics are stimulated to find the values ​​of the serial and parallel resistance. In this study, a sample in the form of solar cell (p-i-n junction) with layer of pure silicon alloy between the structure of microcrystalline silicon and amorphous hydrogenated silicon, referred to short symbol µc(a)-Si:H, in order to improve the performance of hydrogenated amorphous silicon cells. The results showed that the effect of serial resistance on cell performance is weak, while the parallel resistance, a negative role in cell performance with increasing temperature which leads to a decrease in the value of fill factor and hence to a decrease in Power taken from the cell. In other words, at high temperatures, we must ameliorate the performance of this resistance in order to get a high quality cell.